2022
DOI: 10.1080/19420862.2021.2020081
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial membrane potential-enriched CHO host: a novel and powerful tool for improving biomanufacturing capability

Abstract: With the aim of increasing protein productivity of Chinese hamster ovary (CHO) cells, we sought to generate new CHO hosts with favorable biomanufacturing phenotypes and improved functionality. Here, we present an innovative approach of enriching the CHO host cells with a high mitochondrial membrane potential (MMP). Stable transfectant pools and clonal cell lines expressing difficult-to-express bispecific molecules generated from the MMP-enriched host outperformed the parental host by displaying (1) improved fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 78 publications
2
10
0
Order By: Relevance
“…For instance, CHO cells overexpressing key regulatory elements of carbon and energy metabolism (e.g., mTOR or Forkhead box protein A1 [Foxa1]) have achieved large improvement in viable cell densities and recombinant protein production 33 , 34 . Using an enrichment approach based on a high mitochondrial membrane potential (MMP), a new CHO cell host (derived from a CHOK1 host) with increased cell densities, cell viability and productivity of different ‘difficult-to-express’ proteins was developed 35 , 36 . Supplementing culture medium with copper have also led to simultaneous increase in growth and productivity in CHO cells 37 , through mechanisms that that have been proposed to involve enhanced oxidative metabolism 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CHO cells overexpressing key regulatory elements of carbon and energy metabolism (e.g., mTOR or Forkhead box protein A1 [Foxa1]) have achieved large improvement in viable cell densities and recombinant protein production 33 , 34 . Using an enrichment approach based on a high mitochondrial membrane potential (MMP), a new CHO cell host (derived from a CHOK1 host) with increased cell densities, cell viability and productivity of different ‘difficult-to-express’ proteins was developed 35 , 36 . Supplementing culture medium with copper have also led to simultaneous increase in growth and productivity in CHO cells 37 , through mechanisms that that have been proposed to involve enhanced oxidative metabolism 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In bottom-up proteomics, peptide abundance measured via LC-MS/MS is traditionally collapsed into protein abundance, and statistical analysis is then performed on the aggregated protein abundance to infer differentially expressed proteins ( Nesvizhskii et al 2003 , Choi et al 2014 , Tyanova et al 2016 ). The empirical Bayes moderated t -test implemented in the limma R package is among the most commonly used techniques for this purpose ( Ritchie et al 2015 , Nuber et al 2021 , Chakrabarti et al 2022 ). By leveraging the parallel nature of -omics data, this method borrows information across proteins to improve the reliability of conclusions drawn from statistics ( Ritchie et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Technical variability in sample preparation, protein digestion, and instrumental stability can all contribute to the challenges faced by the LC-MS/MS platform, thereby affecting the statistical power of the study ( Piehowski et al 2013 ). Moreover, large inter-subject heterogeneity or subtle yet significant changes within compared cohorts pose additional complications, particularly in clinical settings ( Suh et al 2015 , Chakrabarti et al 2022 , Hristova et al 2023 ). These inherent statistical challenges drive the need for novel computational methods capable of extracting maximum insights from each dataset ( Chandramouli and Qian 2009 , Zhou et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown how redox imbalances affect bioprocessing: improper oxidative folding leads to product aggregation or fragmentation (Gomez et al, 2018; Handlogten, Lee‐O'Brien, et al, 2018), lowered metabolic activity leads to lower productivity (Ali et al, 2020; Chevallier, Andersen, et al, 2020; Templeton et al, 2013, 2017), and oxidation‐induced endoplasmic reticulum stress leads to activation of the unfolded protein response pathway and apoptosis (Chakrabarti et al, 2022; Figueroa et al 2004; Henry et al, 2020; Sinharoy et al, 2021). Several bioprocess parameters can affect cellular redox, including dissolved oxygen, media formulations, feeding schedules, pH, and temperature (Gomez et al, 2010, 2012, 2018; Handlogten et al, 2020; Handlogten, Zhu, et al, 2018; Henry et al, 2020; Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several bioprocess parameters can affect cellular redox, including dissolved oxygen, media formulations, feeding schedules, pH, and temperature (Gomez et al, 2010, 2012, 2018; Handlogten et al, 2020; Handlogten, Zhu, et al, 2018; Henry et al, 2020; Xu et al, 2018). Several studies recently demonstrated methods to overcome deleterious redox effects, including implementing online control of extracellular redox, rebalancing media using multiomics data, creating design‐of‐experiment studies with media supplementations, implementing perfusion platforms, and enriching host pools to contain favorable redox‐resistant phenotypes (Ali et al, 2020; Chakrabarti et al, 2022; Gomez et al, 2019, 2020; Ha et al, 2018; Handlogten et al, 2020; Sinharoy et al, 2020). However, few methods exist to measure changes in intracellular redox and related downstream effects (Sinharoy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%